а) Ответ: х = 0,5;
б) Ответ: у = |3|.
Уравнение а): х + 9/3 - 1,5 = 4х - 5.
Решение:
9/3 = 3; х + (3 - 1,5) = 3 - 1,5 = 1,5;
1,5 = 4х - 5;
(4 - 5)х = 1х;
1 не равняется 1,5; но 1х = 1,5
1,5 - 1 = 0,5;
х = 0,5.
Проверяем:
0,5 + 9/3 - 1,5 = 4х - 5;
1х = 1,5; а как мы знаем 1х = 1,5; значит 1,5 = 1,5
Ответ: х = 0,5.
Уравнение б): |у + 3| = 6.
6 = 3 + у;
6 - 3 = 3;
у = 3;
у = |3|.
|3 + 3| = 6.
Ответ: у = |3|.
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
а) Ответ: х = 0,5;
б) Ответ: у = |3|.
Пошаговое объяснение:
Уравнение а): х + 9/3 - 1,5 = 4х - 5.
Решение:
9/3 = 3; х + (3 - 1,5) = 3 - 1,5 = 1,5;
1,5 = 4х - 5;
(4 - 5)х = 1х;
1 не равняется 1,5; но 1х = 1,5
1,5 - 1 = 0,5;
х = 0,5.
Проверяем:
0,5 + 9/3 - 1,5 = 4х - 5;
1х = 1,5; а как мы знаем 1х = 1,5; значит 1,5 = 1,5
Ответ: х = 0,5.
Уравнение б): |у + 3| = 6.
Решение:
6 = 3 + у;
6 - 3 = 3;
у = 3;
у = |3|.
Проверяем:
|3 + 3| = 6.
Ответ: у = |3|.